Contested riverscapes in Jakarta: flooding, forced eviction and urban image. Issue 3 (2nd September 2019) - Dovey, Kim; Cook, Brian; Achmadi, Amanda
ABSTRACT: This paper investigates the ways that intersecting desires to control flooding, evict informal settlements and build a modern global city play out in Jakarta. We explore resistance to eviction in two riverbank settlements: in one case playing by the formal rules led to a legal win but a loss of livelihood; the more successful case was self-organized and involved multiple tactics including partial self-demolition, media engagement and a re-branding of the kampung. We demonstrate the ways assemblage thinking can contribute understanding of the intersection of formal and informal practices, along with the struggles of the urban poor to resist eviction and maintain livelihoods.